Should Code be Released? - McCafferty, Dennis (Communications of the ACM, 2010)
This article reports on the development of computer software codes and the arguments as to whether they should be released by researchers. The software codes give insight into research methodology during the peer review process for research, but there is disagreement as to whether the computer codes should be released because, most of the time, they were not developed by the researchers themselves. The article discusses the practices, procedures, and standards of software programming, noting problems with liability for errors. Information is also provided on the protection of intellectual property, as well as on research on climate change and nanotechnology.